Dividend Discount Model (Ddm) Sebagai Model Penilaian Harga Saham (Studi empiris pada perusahaan-perusahaan BUMN yang listing di BEI) - C Ambar Pujiharjanto; Nilmawati Nilmawati (Universitas Muhammadiyah Yogyakarta, 2010)
A valuation model is a mechanism that converts a set of forecast a series of company and economic variables into a forecast of market value for the company’s stock. This purpose of this paper to evaluate intrinsic value of stock are used dividend discount model (DDM) and so to compare at market stock price. BUMN firms are used at this research object because covering all industrial situation. The DDM was operationalised to test on nine BUMN firms and based on the result it is found that eight BUMN firms are undervalued and one BUMN firm is overvalued.